Right of Children to Free and Compulsory Education Act (RTE) : A Review - Kaur, Dr. Preetinder (Innovative Research Thoughts, 2018)
Indian Parliament approved the “Right of Children to Free and Compulsory Education Act (RTE) on August 4th, 2009, which outlines the necessity of free and compulsory education for children between the ages of 6 and 14 in India. The Act was signed into law on April 1, 2010, making India one of 135 nations where education is a basic right for all children.